Spontaneous pregnancy rates in infertile women after sequential hydrosonography and hysterosalpingo-foam sonography. (April 2022) - Melcer, Yaakov; Shamir-Kaholi, Neta; Vainer-Rotbart, Shirah; Pekar-Zlotin, Marina; Youngster, Michal; Gat, Itai; Maymon, Ron
Abstract: Objective: To determine the clinical pregnancy rate following sequential hydrosonography and hysterosalpingo-foam sonography (HyFoSy) in tubal patency assessment among women undergoing infertility work-up. Study design: Prospective follow-up of women referred to our department between July 2019 and October 2020. Sequential hydrosonography and HyFoSy were carried out. Results: Out of 250 having the procedure, 100 women were excluded from study due to limited infertility, semen abnormal or not examined, evaluation for social egg freezing or they were single. Of the remaining 150 women, 48 (32%) conceived during a 10–24 months follow-up period: 17 (11%) conceived naturally and 7 (4.7%) by IUI. The mean time to conception was 5.5 ± 5.4 months and the pregnancy rate was 52% within 6 months. Among the spontaneous pregnancies 47% occurred within a month and 76% within 3 months. Conclusion: Sequential hydrosonography and HyFoSy is a promising method for assessing the uterine cavity and tubal patency in women undergoing infertility workup. The findings suggest that the procedure may increase the chance of a spontaneous pregnancy following the procedure. Given the other known advantages of sequential hydrosonography and HyFoSy, this test is worth including in the initial workup for infertile patients.